The Domicile Requirement for Village Heads After Constitutional Court Decision No. 128/PUU-XIII/2015 and Its Implications for the Administration of Village Governance - Rut Simatupang; Janpatar Simamora; Hisar Siregar (Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the dynamics of regulating domicile requirements for Village Head candidates and their implications following Constitutional Court Decision Number 128/PUU-XIII/2015 on village governance. Although the decision removed domicile restrictions to guarantee equal constitutional rights, previous studies have focused more on its normative and constitutional aspects than on its sociological impact on village communities with strong local values. This study fills that gap by examining how the removal of domicile requirements affects social acceptance, leadership legitimacy, and the effectiveness of village governance. Using an empirical juridical method with a descriptive qualitative approach, this research collected primary data through in-depth interviews with community leaders, village officials, and villagers, while secondary data were obtained from regulatory documents and relevant literature. The findings show that the implementation of the Court’s decision is still marked by social resistance, as communities tend to trust local candidates more because they are considered to better understand village customs and social conditions. At the same time, the inclusion of non-local candidates has encouraged higher competency standards in village political competition. The novelty of this study lies in showing that the implications of the Court’s decision extend beyond the protection of constitutional rights to include changes in social legitimacy and leadership effectiveness at the village level. These findings are significant in indicating that effective village governance depends not only on managerial competence, but also on the elected Village Head’s ability to adapt to local wisdom and community values.